A pilot study of Coxiella seroprevalence in occupationally exposed individuals in the Peace River region of Alberta and British Columbia - Houston, Ilona; Barlund, Christy; Saxinger, Lynora; Wood, Heidi; Houston, Stan (Canadian veterinary journal, 2018)
A pilot seroprevalence study was performed among asymptomatic occupationally exposed individuals in June, 2016 in the Peace River region of Alberta and British Columbia. Five of 40 subjects - 3 of 24 small ruminant producers, 1 of 14 abattoir workers, and 1 of 2 veterinarians had evidence of exposure. More systematic surveillance and more active promotion of biosecure husbandry methods should be considered.